Supplementation of dietary Angelica sinensis extracts to lactating Wuzhishan sows: effects on milk composition, immune function, milk-derived hormones, and related gene expression - Wu, Hongzhi; Yu, Xilong; Zhang, Xiaoyu; Peng, Weiqi; Ji, Fengjie; Shen, Qian; Lv, Renlong (Frontiers in Veterinary Science, 2025)
The milk provided by sows plays an essential role in the growth and development of the piglets. This study aimed to explore the effects of Angelica sinensis extracts on milk composition, immune function, milk-derived hormones, and related gene expression of lactating sows. Forty-eight sows were randomly allocated into four groups, with six replicates and two sows per replicate. The control group (CON) was fed basal experimental diets, and the experimental groups were fed 400, 600, and 800 mg/kg Angelica sinensis extracts in powder (AS1, AS2, and AS3, respectively). Compared to the CON, (1) the lactoprotein and milk fat contents were higher (p < 0.05) in AS1, AS2, and AS3 at 12 and 24 h, and on the 7th day; (2) the IgA, IgG, and IL-2 levels were higher (p < 0.05), and the TNF-α levels were lower (p < 0.05) in AS1, AS2, and AS3 at 12 and 24 h; the IgG, IgM, and IL-2 levels were higher (p < 0.05) in AS1, AS2, and AS3 on the 7th day; (3) the progesterone, prolactin, growth hormone, and insulin-like growth factor-1 contents were higher (p < 0.05) in AS1, AS2, and AS3 at 12 and 24 h; the growth hormone and insulin-like growth factor-1 contents were higher (p < 0.05) in AS2 and AS3 on the 7th day; (4) the relative expressions of PRLP, LALBA, AKT1, FASN, GLUT1, and CSN2 in mammary tissue were higher (p < 0.05) in groups treated with Angelica sinensis extracts; (5) the serum IgA, IgM, IL-6, growth hormone, insulin, and insulin-like growth factor-1 contents were higher (p < 0.05) in AS2 and AS3 in piglets; and (6) the relative expressions of PRLP and IL-10 in umbilical cord were higher (p < 0.05) in groups treated with Angelica sinensis extracts. Incorporating 600 mg/kg of Angelica sinensis extracts into the diets of lactating Wuzhishan sows elicited differential responses regarding milk composition, immune function, hormonal profiles, and associated gene expression across distinct postpartum periods.